The importance of entrepreneurship in nursing (Research, Society and Development, 2022)
The Brazilian health system, compared to the rest of the world, is fraught with limitations and numerous organizational difficulties. These difficulties stem from the harsh economic conditions, which directly impact the development of the Brazilian healthcare market. Colleges do not develop the commercial part of the nurse, which can be responsible for the inability to embrace entrepreneurial nursing opportunities in building a robust, functional and sustainable health system. The objective of the study is to describe the importance of entrepreneurship in Nursing. The methodology used was a bibliographic review in the Google Scholar database, BVS and SciELO, published between 2015 and 2021, available in full. Initially, 125 studies were found and after applying the filters, according to the inclusion and exclusion criteria, 104 studies were eliminated. Duplicate studies, monographs, handouts and books were not considered. At the end, 21 scientific articles were included. The concept of entrepreneurship in nursing goes against the general concept of entrepreneurship. The entrepreneurial nurse follows the perspectives of creation, generation and development of an opportunity focused on nursing actions, it is mainly linked to personal characteristics, which allows associating entrepreneurship with a nurse's behavior. Nurses have many reasons to choose the path to entrepreneurship as being an area that has a holistic, broad and transversal vision of the patient's needs is having the competence to enter new spaces, together with the question that the human being will need specific care and professional, at some point in life.